2011
DOI: 10.1051/0004-6361/201117382
|View full text |Cite
|
Sign up to set email alerts
|

Systematics in lensing reconstruction: dark matter rings in the sky?

Abstract: Context. Non-parametric lensing methods are a useful way of reconstructing the lensing mass of a cluster without making assumptions about the way the mass is distributed in the cluster. These methods are particularly powerful in the case of galaxy clusters with a large number of constraints. The advantage of not assuming implicitly that the luminous matter follows the dark matter is particularly interesting in those cases where the cluster is in a non-relaxed dynamical state. On the other hand, non-parametric … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Moreover, this disagrees with the results found for other extensively studied clusters, such as the Bullet Cluster (e.g., Markevitch et al 2002) or clusters CL 0152-1357 and MS 1054-0321 (Jee et al 2005a,b), where a coincidence is found between the galaxy and dark matter distributions. Nevertheless, the peculiarity of A1995 is not so extreme as in other clusters, such as CL 0024+17, where evidence was found for a dark matter ring (Jee et al 2007) without a obvious galaxy counterpart (Qin et al 2008; but see also Ponente & Diego 2011, who suggest that dark matter ringlike structures could be due to systematics in lensing reconstruction). In any case, the observed dichotomy between the dark matter and galaxy distributions makes A1995 an appealing target for future studies.…”
Section: Merger Kinematics and Diffuse Radio Sourcesmentioning
confidence: 85%
“…Moreover, this disagrees with the results found for other extensively studied clusters, such as the Bullet Cluster (e.g., Markevitch et al 2002) or clusters CL 0152-1357 and MS 1054-0321 (Jee et al 2005a,b), where a coincidence is found between the galaxy and dark matter distributions. Nevertheless, the peculiarity of A1995 is not so extreme as in other clusters, such as CL 0024+17, where evidence was found for a dark matter ring (Jee et al 2007) without a obvious galaxy counterpart (Qin et al 2008; but see also Ponente & Diego 2011, who suggest that dark matter ringlike structures could be due to systematics in lensing reconstruction). In any case, the observed dichotomy between the dark matter and galaxy distributions makes A1995 an appealing target for future studies.…”
Section: Merger Kinematics and Diffuse Radio Sourcesmentioning
confidence: 85%
“…Here we outline briefly WSLAP+ for the mass reconstruction and refer the reader for details of its implementation in our previous papers (Diego et al 2005a(Diego et al , 2005b(Diego et al , 2007(Diego et al , 2015aPonente & Diego 2011;Sendra et al 2014).…”
Section: Free-form Lensing Modelmentioning
confidence: 99%
“…Diego et al 2005; Coe et al 2008; Merten et al 2009) are novel in the sense that they are assumption free and highly flexible (e.g. Coe et al 2010; Ponente & Diego 2011), and methods based directly on arc morphologies yield high‐resolution results (see also Grillo et al 2010). The parametric method presented here is simply aimed to produce the critical curves in an automated way based on simple physical considerations (and thus is capable of finding multiple images as we have shown constantly before), and constitutes another important step towards the ability to deduce the lensing properties of clusters in large sky surveys in an automated way, so that we aim now to present the first observationally deduced, universal distribution of Einstein radii.…”
Section: Introductionmentioning
confidence: 99%